Cardiac autonomic functioning and clinical outcome in adolescent borderline personality disorder over two years - Sigrist, Christine; Reichl, Corinna; Schmidt, Stefanie; Brunner, Romuald; Kaess, Michael; Koenig, Julian (Progress in neuro-psychopharmacology & biological psychiatry, 2021)
The present study aimed to expand on previous findings that pre-treatment autonomic nervous system (ANS) functioning serves as a predictor of clinical outcome in adolescent borderline personality disorder (BPD), while examining whether the relationship between ANS functioning and treatment outcome may vary as a function of early life maltreatment (ELM). ANS stress response was examined considering changes in heart rate (HR) and vagally-mediated heart rate variability (vmHRV) over different conditions of the Montreal Imaging Stress Task (MIST) in a clinical sample of N = 27 adolescents across the spectrum of BPD severity. Participants received in- and/or outpatient treatment, while clinical data was assessed at routine follow-ups. Clinical outcome was defined by change in the number of fulfilled BPD criteria (as measured using the SCID-II), severity of psychopathology (CGI-S), and global level of functioning (GAF), measured 12 and 24 months after baseline assessments. Mixed-effects (random-intercept/random slope) linear regression models were calculated to examine markers of ANS function as potential predictors of clinical outcome. Irrespective of the presence of ELM exposure, both vmHRV resting-state and stress recovery measures were identified as significant predictors of clinical outcome over time. This study adds to the existing literature by replicating and expanding on preliminary findings, considering also physiological reactivity and recovery in addition to resting-state measures of ANS functioning. The present results further highlight the potential of markers of ANS functioning to serve as objective measures in the process of monitoring patient progress and to make predictions regarding treatment outcome in psychiatry research.